Perlindungan Hukum bagi Konsumen dalam Transaksi Jual Beli melalui Media Elektronik dengan Sistem â€Dropshipâ€ - Gusti Ayu Dwi Dhyana Amrita; Ni Luh Made Mahendrawati; Ni Made Puspasutari Ujianti (Warmadewa Press, 2020)
The activity of buying and selling using the dropshipping system is a trading activity in which the seller does not have stock of the goods he is selling, but only promotes goods through images uploaded to his or her online shop. If the seller gets an order from a consumer, the seller cannot directly confirm the condition of the goods to be sent to the consumer because the supplier who will send it uses the seller's identity. This study aims to determine and study legal protection for consumers in buying and selling via electronic media using the dropshipping system, and to find out and study the legal consequences that arise if there is default in buying and selling via electronic media using the dropshipping system. The results showed that legal protection for consumers in buying and selling through electronic media using the dropshipping system can be done in a preventive and repressive manner, and the legal consequences that arise if there is default in buying and selling using the dropshipping system, namely the loss suffered by consumers is the responsibility of the seller because The seller is the party who makes a direct agreement with the consumer, not the supplier. Therefore, the public is expected to be more careful in conducting transactions via electronic media so that they do not suffer their own losses.